Pengaruh Motivasi Investasi Dan Perilaku Keuangan Terhadap Keputusan Investasi Mahasiswa Jurusan Akuntansi Pada Universitas Pendidikan Ganesha - Riski Widyaswara, Kadek Mas; Dewi, Ni Wayan Yulianita; Sinarwati, Ni Kadek (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aimed to examine "The Influence of Investment Motivation and Financial Behaviour on Investment Decisions of Accounting Students at Ganesha University of Education." A causal quantitative design was employed in this research. The sample consisted of 72 respondents, selected using a saturation sampling technique. Data were collected through questionnaires and analysed using multiple linear regression. The results show that (1) investment motivation has a positive and significant effect on the investment decisions of accounting students at Ganesha University of Education, and (2) financial behaviour also has a positive and significant effect on their investment decisions. These findings indicate that there is a partial influence of investment motivation on investment decisions, meaning the first hypothesis is accepted. In addition, there is a partial influence of financial behaviour on investment decisions, which confirms the acceptance of the second hypothesis.